2019
DOI: 10.1029/2019jg005212
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Processing of Sediment‐Derived Dissolved Organic Matter: Implications for Its Subsequent Biogeochemical Cycling in Overlying Seawater

Abstract: Coastal sediments contain a large amount of dissolved organic matter (DOM), which can be mobilized into the overlying water by natural and anthropogenic activities. The bioavailability and subsequent biogeochemical effects of this sediment-derived DOM are unclear. To investigate those, we collected a sediment pore-water DOM (SDOM) sample and its overlying seawater to conduct a bioassay experiment, which allowed tracking of both short-term and long-term microbial processes in the context of DOM transformations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 72 publications
(111 reference statements)
4
32
0
Order By: Relevance
“…The main changes of the DOM molecular composition were observed along the time axis of the experiments (Figure 3). The decomposition of bulk organic compounds and molecules that were probably liberated by slurrying led to a gradual removal of bio-available components, accompanied by a relative accumulation of more refractory compounds [66,70]. Despite the clear alteration of the DOM composition by the slurry process, DOM analysis revealed that prophage induction had modified the chemical composition and character of the benthic DOM pool, which is in line with previous studies [12,20,71].…”
Section: Viral Lysis and Subsequent Microbial Processes Were Imprintesupporting
confidence: 87%
“…The main changes of the DOM molecular composition were observed along the time axis of the experiments (Figure 3). The decomposition of bulk organic compounds and molecules that were probably liberated by slurrying led to a gradual removal of bio-available components, accompanied by a relative accumulation of more refractory compounds [66,70]. Despite the clear alteration of the DOM composition by the slurry process, DOM analysis revealed that prophage induction had modified the chemical composition and character of the benthic DOM pool, which is in line with previous studies [12,20,71].…”
Section: Viral Lysis and Subsequent Microbial Processes Were Imprintesupporting
confidence: 87%
“…Increasing studies of microbial metabolism have explained the production of RDOM (Lechtenfeld et al ., 2015, Osterholz et al ., 2015, Jiao et al ., 2018, Koch et al ., 2014). At the ecological level, marine microbial communities have been observed following predictable patterns (or recurrent patterns), involving complex network interactions in natural environments (Fuhrman et al ., 2015, Teeling et al ., 2016) and playing an important role in mediating organic carbon from the labile state to the relatively recalcitrant (Cai et al ., 2019). In addition, it has been previously suggested that the RDOM production could be independent of its ultimate sources (Koch et al ., 2005, Rossel et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Organic sulfur is the second most important reduced sulfur pool in sedimentary environments. FT-ICR-MS has shown that organic sulfur in surficial sediments is composed of a heterogeneous mixture of sulfur compounds (Cai et al, 2019). These compounds are considerably different from sulfur compounds identified in seawater.…”
Section: Revealing Organosulfur Cycling In the Dark Ocean And Sedimentmentioning
confidence: 96%
“…The most important biologically mediated processes regulating the long term storage of organic matter in the ocean are the biological carbon pump (Ducklow et al, 2001) and the microbial carbon pump (Jiao et al, 2010(Jiao et al, , 2014(Jiao et al, , 2018. After the long-term incubation (110 days) of a microbial community in natural seawater, more sulfur metabolites may be produced, suggesting that biotic process lead to the formation of refractory compounds (Figure 5A) (Cai et al, 2019). SQDG is efficiently removed as it sinks to the deep sea; in contrast, around 40 sulfur-containing lipids, likely produced by photoautotrophs in the upper ocean, are potentially important as deep-ocean carbon storage compounds (Schubotz et al, 2018).…”
Section: Revealing Organosulfur Cycling In the Dark Ocean And Sedimentmentioning
confidence: 99%